Model dan Implementasi Geographic Information System untuk Pemetaan UMKM di Kabupaten Garut - Fakhrun Shiddieq, Diqy; Roji, Fikri Fahru; Wufron, Wufron; Bekti, Surya Garian (Jurnal Algoritma, 2023)
Usaha Mikro Kecil dan Menengah (UMKM) have an important role in the economy in Indonesia. UMKM have a significant contribution to national gross domestic product (PDB) and encourage the creation of new jobs. Based on data, more than half of the MSMEs in Indonesia are on the island of Java. Garut Regency is one of the regions in West Java which has more than 200 thousand UMKM with various products. UMKM products owned include wickerwork, weaving, specialty foods, leather centers and others. The Garut Regency area is quite large and it is noted that the distribution of UMKM is not centralized. So that stakeholders and the government experience difficulties in planning, implementing and evaluating programs designed to encourage increased performance of UMKM. Researchers found the urgency of research that had not been fully tested empirically and an ideal model had not been produced, so it was felt necessary to carry out this research. Previous research was carried out only on certain UMKM, namely the partial implementation of the Geographic Information System (GIS) for Garut Regency UMKM. However, overall UMKM data has not been found, so this is a novelty in this research. The methodology used is a prototype which has three main processes, namely listening to customer needs, building software and testing. The result of this research is to build a web-based geographic information system for the distribution of UMKM in Garut Regency which is expected to help understand the condition of UMKM better.